Prediction of crystal structures and motifs in the Fe–Mg–O system at Earth's core pressures. (17th June 2021) - Wang, Renhai; Sun, Yang; Wentzcovitch, Renata M; Zheng, Feng; Fang, Yimei; Wu, Shunqing; Lin, Zijing; Wang, Cai-Zhuang; Ho, Kai-Ming
Abstract: Fe, Mg, and O are among the most abundant elements in terrestrial planets. While the behavior of the Fe–O, Mg–O, and Fe–Mg binary systems under pressure have been investigated, there are still very few studies of the Fe–Mg–O ternary system at relevant Earth's core and super-Earth's mantle pressures. Here, we use the adaptive genetic algorithm (AGA) to study ternary Fe x Mg y O z phases in a wide range of stoichiometries at 200 GPa and 350 GPa. We discovered three dynamically stable phases with stoichiometries FeMg2 O4, Fe2 MgO4, and FeMg3 O4 with lower enthalpy than any known combination of Fe–Mg–O high-pressure compounds at 350 GPa. With the discovery of these phases, we construct the Fe–Mg–O ternary convex hull. We further clarify the composition- and pressure-dependence of structural motifs with the analysis of the AGA-found stable and metastable structures. Analysis of binary and ternary stable phases suggest that O, Mg, or both could stabilize a BCC iron alloy at inner core pressures.